Mechanisms of isomerization and oxidation in heated trilinolein by DFT method. Issue 17 (28th March 2019) - Li, Changmo; Ma, Guiting; Yao, Yunping; Liu, Wentao; Zhou, Hang; Mu, Hongyan; Wang, Shuo
Abstract : In order to investigate the molecular mechanisms of the heat-induced cis / trans isomerization and oxidative cleavage of trilinolein, a highly purified sample was heated at a range of temperatures (120, 140, 160, 180, 200, 220 °C) for 5 h. Abstract : In order to investigate the molecular mechanisms of the heat-induced cis / trans isomerization and oxidative cleavage of trilinolein, a highly purified sample was heated at a range of temperatures (120, 140, 160, 180, 200, 220 °C) for 5 h. The reaction process of cis / trans isomerization of C18:2 was studied by a combination of the gas chromatogram (GC) method with density functional theory (DFT). When trilinolein was heated to 180 °C, a small amount of trans / trans C18:2 was obtained (0.074 mg g −1 ). As the temperature increased to 220 °C, the amount of trans C18:2 reached 0.198 mg g −1 . This study shows that C18:2-9c12t and C18:2-9t12c were the main trans fatty acids in heated trilinolein. The molecular mechanisms of isomerization and oxidative cleavage were verified by Gaussian 09 W software. All the geometry was optimized using DFT at the B3LYP/6-31*G level. The energy difference between cis and trans linoleic acid was equal to 6.2 kJ mol −1 . Therefore, vegetable oil with a higher linoleic acid content should be maintained at 140 °C or less to avoid the formation of trans linoleic acid.